Pengaruh Pertumbuhan Ekonomi, Suku Bunga dan Inflasi Terhadap Harga Saham Perusahaan Manufaktur di Indonesia Tahun 2021-2023 - Azizah Inas Pratiwi; Sri Murwanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of economic growth, interest rates, and inflation on the stock prices of manufacturing companies in Indonesia from 2021 to 2023. The methodology used in this study is a quantitative approach utilizing secondary data in the form of annual financial reports of companies obtained from the official website of the Indonesia Stock Exchange (IDX) as well as other supporting sources. The sample selection in this study was carried out using a random sampling method, and the analysis was conducted using SPSS software. The results of the study indicate that economic growth and interest rates have a significant effect on stock prices, thus H1 and H2 are accepted; conversely, inflation does not have a significant effect on stock prices,so H3 is rejected